AB0407 Combined serum free light chains are associated with active disease in systemic lupus erythematosus. (23rd January 2014) - Assi, L. K.; Lisnevskaia, L.; Powner, D.; Ross, E.; Hughes, R. G.; Rahman, A.; Isenberg, D.
Abstract : Background: Systemic lupus erythematosus (SLE) is characterised by chronic B cell stimulation and hyperactivity. Due to the complexity and variability observed during the course of SLE, reliable and accurate biomarkers for diagnosis and disease management are required. Previously, increased concentrations of polyclonal serum free light chains (FLC), a marker of immune status and renal function, have been reported to be elevated in SLE patients 1 . Objectives: To compare FLC levels in SLE patients with routine biomarkers of disease activity. Methods: Sera were collected from SLE patients (N=56) who fulfilled the revised ACR criteria for the classification of SLE. Samples were analysed for combined FLC (cFLC; κ plus λ, Freelite®, The Binding Site Group Ltd) and compared to conventional biomarkers of SLE disease activity notably anti-dsDNA antibodies (measured by ELISA), C3 (laser nephelometer), lymphocyte count and erythrocyte sedimentation rate (ESR) as well as to total levels of IgG, IgA and IgM. Cystatin C was analysed as a marker of renal function (The Binding Site Group Ltd). Serologically active disease was defined as patients with elevated anti-dsDNA antibody levels (>50IU/ml) together with reduced C3 (<0.9g/L). Results: The population had a median age of 43 years (range: 21-86). 89% of the population were female and 52% were Caucasian. The median concentration of cFLC was 37.96mg/L (15.96-173.73mg/L; median concentration in a healthy population: 20mg/L). A moderate correlation was observed between cFLC vs: ESR (spearman r: 0.484, p<0.001), cystatin C (r: 0.39, p=0.002), IgG (r: 0.55, p<0.001) and IgA (r: 0.63, p<0.001). However, cFLC did not correlate with anti-dsDNA antibodies (r: 0.2, p=0.07), C3 (r: -0.08, p=0.572), lymphocyte count (r: -0.09, p=0.535) or IgM (r: 0.003, p=0.980). cFLC levels were significantly elevated in patients with serologically active disease (N=14, 25%): median: 59.79mg/L (15.96-140.96mg/L) vs 33.78mg/L (16.99-173.73mg/L), p=0.01. Interestingly, there was no significant difference in the levels of IgG (p=0.343), IgA (p=0.407), IgM (p=0.953), ESR (p=0.464) or cystatin C (p=0.465) in patients with serologically active vs inactive disease. Conclusions: cFLC concentrations are elevated in SLE patients with serologically active disease and therefore could be used as a marker of disease activity. Future work is warranted to determine how cFLC can be used to monitor disease progression. References: Aggarwal R, Sequeira W, Kokebie R et al. Serum free light chains as biomarkers for systemic lupus erythematosus disease activity. Arthritis Care Res 2011;63:891-898. Disclosure of Interest: L. Assi Employee of: The Binding Site Group Ltd, L. Lisnevskaia: None Declared, D. Powner Employee of: The Binding Site Group Ltd, E. Ross: None Declared, R. Hughes Employee of: The Binding Site Group Ltd, A. Rahman: None Declared, D. Isenberg: None Declared